2017
DOI: 10.1177/1538574417712648
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Predictors of Reintervention After EVAR: Guidance for Risk-Stratified Surveillance

Abstract: Existing data on predictors of post-EVAR complications are generally of poor quality and largely derived from retrospective studies. Few studies describing suggestions for stratified surveillance have been subjected to external validation. There is a need to refine risk prediction for EVAR failure and to conduct prospective comparative studies of personalized surveillance with standard practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…2,3,8,10) Many reported cases were defined as an enlargement of the AAA diameter above 5 mm and were indicated as secondary reintervention. 11) Late OC was considered a final option when the secondary endovascular procedure failed. There was no clear indication of the aneurysm size in the OC, especially type II endoleaks, but a diameter >65 mm was a risk factor for new onset type I endoleaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,8,10) Many reported cases were defined as an enlargement of the AAA diameter above 5 mm and were indicated as secondary reintervention. 11) Late OC was considered a final option when the secondary endovascular procedure failed. There was no clear indication of the aneurysm size in the OC, especially type II endoleaks, but a diameter >65 mm was a risk factor for new onset type I endoleaks.…”
Section: Discussionmentioning
confidence: 99%
“…There was no clear indication of the aneurysm size in the OC, especially type II endoleaks, but a diameter >65 mm was a risk factor for new onset type I endoleaks. 11) The initial experience with a late OC reported that the procedure-related mortality rate was as high as 17%, and it was considered a hazardous procedure. 12) A recent literature review showed that the 30-day mortality rate was 9.1%.…”
Section: Discussionmentioning
confidence: 99%
“…EVAR procedures can be challenging and, at times, extraordinarily difficult. They require seasoned endovascular experience and refined skills (3) . Of all endovascular procedures, meticulous assessment of anatomy and preoperative procedure Case Report planning are absolutely paramount to produce optimal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2 EVAR is also correlated with a higher reintervention rate, which can be as high as 20% in the first 5 years. 3 Endoleaks constitute the main cause of reinterventions. 4 It is often unclear which type of endoleak is the correct diagnose, 5 making the treatment decision difficult.…”
Section: Introductionmentioning
confidence: 99%